Fact-finding without facts the uncertain evidentiary foundations of international criminal convictions - Combs, Nancy A. 1965- (Cambridge [U.K.] Cambridge University Press, 2010)
"This book explores international criminal fact-finding to reveal that criminal trials are beset by impediments that impair their ability to determine who did what to whom"--Provided by publisher.
"Fact-finding Without Facts explores international criminal fact-finding - empirically, conceptually, and normatively. After reviewing thousands of pages of transcripts from various international criminal tribunals, the author reveals that international criminal trials are beset by numerous and severe fact-finding impediments that substantially impair the tribunals' ability to determine who did what to whom. These fact-finding impediments have heretofore received virtually no publicity, let alone scholarly treatment, and they are deeply troubling not only because they raise grave concerns about the accuracy of the judgments currently being issued but because they can be expected to similarly impair the next generation of international trials that will be held at the International Criminal Court. After setting forth her empirical findings, the author considers their conceptual and normative implications. The author concludes that international criminal tribunals purport a fact-finding competence that they do not possess, and as a consequence, base their judgments on a less precise, more amorphous method of fact-finding than they publicly acknowledge. The book ends with an exploration of various normative questions, including the most foundational: whether the international tribunals' fact-finding impediments fatally undermine the international criminal justice project"--Provided by publisher.
The evidence supporting international criminal convictions -- Questions unanswered : international witnesses and the information unconveyed -- The educational, linguistic, and cultural impediments to accurate fact-finding at the international tribunals -- Of inconsistencies and their explanations -- Perjury : the counternarrative -- Expectations unfulfilled : the consequences of the fact-finding impediments -- Casual indifference : the trial chambers' treatment of testimonial deficiencies -- Organizational liability revived : the pro-conviction bias explained -- Help needed : practical suggestions and procedural reforms to improve fact-finding accuracy -- Assessing the status quo : they are not doing what they say they are doing but is what they are doing worth doing?
Keywords: International Criminal Court; Evidence, Criminal; International criminal courts